Influence of exposure time on phosphorus composition and bioavailability in wetland sediments from Poyang lake, since the operation of the Three Gorges Dam. (August 2020) - Ni, Zhaokui; Wang, Shengrui; Wu, Yue; Liu, Xiaofei; Lin, Ripeng; Liu, Zhezhe
Abstract: The role of exposure time on wetland sediment-bound phosphorus (P) biogeochemical behavior is studied in Lake Poyang after the operation of the Three Gorges Dam (TGD). The multiple P compounds primarily include orth–P (88.3%), mono–P (8.9%), DNA–P (2.1%), and pyro–P (0.8%) in the exposed sediments. A significant decreasing trend of orth–P occurred after the operation of the Three Gorges Dam (TGD), with the mean concentration decreasing from 175.9 to 142.5 mg kg −1 from 2007 to 2012 (ANOVA: P  < 0.05), whereas the temporal change in biogenic P showed great variability. The plant distribution pattern and the increase in plant biomass due to decreased water levels might be the reason that caused variations in the P species. Furthermore, the content of orth–P, mono–P, DNA–P, and pyro–P showed increasing trends as sediment exposure time increased. However, the enzyme hydrolysis rate of DNA–P decreased with exposure time and may cause the bioavailability of biogenic P to decrease. Despite the fact that the bioavailability of biogenic P might decline in the short term, the favorable environmental conditions for P release in sediment rewetting processes, together with the increase in orth–P and biogenic P due to extended exposure time, indicate that these large additions of P would enter the overlying water and cause water quality decline once the sediment is submerged underwater during the next wet season. An environmental process analysis showed that the increased exposure time induced sediment environmental conditions changes that played an important role in the biogeochemical cycle of P and may be an important way of P replenishment in Lake Poyang. The results of this study help provide a better understanding of the role of sediment drying/wetting cycles in nutrient biogeochemical behavior and fates in wetland ecosystems. Graphical abstract: Image 1 Highlights: The role of sediment exposure time differences on phosphorus (P) biogeochemical behavior was studied. Increased exposure time enhanced sediment total phosphorus (TP) and P species accumulation. The bioavailability of biogenic P might decrease with sediment exposure time. Sediment release caused by extended exposure time is essential to water P replenishment. Abstract : Increased exposure time induced sediment environment condition changes played an important role in biogeochemical cycle of P and may be an important way of P replenishment in Lake Poyang.